Experimental acute canine monocytic ehrlichiosis: clinicopathological and immunopathological findings - de Castro, M. B.; Machado, R. Z.; de Aquino, LPCT; Alessi, A. C.; Costa, M. T. (Elsevier B.V., 2004)
Clinical signs, humoral and cellular immune responses, and microscopic and gross tissue alterations resulting from acute experimental Ehrlichia canis infection in dogs were studied. Four dogs were inoculated with E canis and four were used as uninfected controls. After a 10-14-day incubation period, infected dogs developed pyrexia up to 41 degreesC for 6-8 days. Antibody titers to E. canis antigen were demonstrable in all inoculated dogs at 30 days post-infection. Necropsy of infected animals revealed pale mucous membranes, generalized lymphadenopathy, splenomegaly, edema and ascites. Microcopically, the main lesions were: lymphoreticular hyperplasia in cortical areas of lymph nodes and spleenic white pulp, periportal accumulation of mononuclear cells and centrolobular fatty degeneration of the liver. Kidneys presented with glomerulonephritis characterized by interstitial, mononuclear infiltration. Immunophenotyping of lymphocytes from lymph nodes and spleen sections displayed alterations in IgG, IgM, CD3+ and CD8+ cells population in infected dogs. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Ehrlichia canis; ehrlichiosis; dog; immunopathology; Immunohistochemistry